2006
DOI: 10.1038/sj.jcbfm.9600388
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Translation Arrest in the Reperfused Brain

Abstract: Irreversible translation arrest occurs in reperfused neurons that will die by delayed neuronal death. It is now recognized that suppression of protein synthesis is a general response of eukaryotic cells to exogenous stressors. Indeed, stress-induced translation arrest can be viewed as a component of cell stress responses, and consists of initiation, maintenance, and termination phases that work in concert with stress-induced transcriptional mechanisms. Within this framework, we review translation arrest in rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 146 publications
(409 reference statements)
3
77
0
Order By: Relevance
“…However, the question remains if there is a relationship between SGs and PAs. Each may contribute to translation arrest in parallel, but an interaction between PAs and SGs has not been ruled out (DeGracia and Hu, 2006). Thus, we report here studies of pairwise colocalization of ubiquitin, a marker of PAs, and TIA-1 and the 40S protein S6, as markers of SGs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the question remains if there is a relationship between SGs and PAs. Each may contribute to translation arrest in parallel, but an interaction between PAs and SGs has not been ruled out (DeGracia and Hu, 2006). Thus, we report here studies of pairwise colocalization of ubiquitin, a marker of PAs, and TIA-1 and the 40S protein S6, as markers of SGs.…”
Section: Introductionmentioning
confidence: 98%
“…Recent evidence points to the partitioning of ribosomes into translationally nonfunctional subcellular structures, including protein aggregates (PAs) and stress granules (SGs), as potential causes for the lack of recovery of normal protein synthesis in reperfused CA1 (reviewed in DeGracia and Hu, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Under electron microscopy (EM), visible protein aggregates progressively accumulate in some CA1 neurons and accumulation of the aggregates seem to occur primarily in neurons destined to undergo delayed neuronal death after brain ischemia. Further evidence [56,57] showed that the endoplasmic reticulum (ER), mitochondria and cytoplasm all respond to the accumulation of unfolded proteins by compartment-specific signaling pathways to participate in neuronal injury, whereas ubiquintin-proteasome as well as beneficial chaperones function to prevent protein aggregation and assist in protein folding [58,59] . Furthermore, by utilizing a rat transient cerebral ischemic preconditioning model, Liu et al found that ischemic preconditioning significantly reduced protein aggregation in CA1 neurons after ischemia.…”
Section: Heat Shock Proteins (Hsps)mentioning
confidence: 99%
“…There is thought to be a temporal window in which reversal or prevention of induction of the apoptotic cascade can occur, and such prevention of cell death would improve functional outcome [66]. Transient translational arrest is a component of the acute response to ischemia/reperfusion, which, together with the induction of the heat shock family of proteins, serves to limit the production of unfolded/misfolded proteins, thereby inhibiting the induction of pro-death pathways [67,68].…”
Section: B Cerebral Ischemia and Mirnasmentioning
confidence: 99%